Microstructure and texture development in AISI430 ferritic stainless steel - Masindi, Rabelani Rofhiwa (Centre for Materials Engineering, 2017)
AISI 430 ferritic stainless steel (FSS) is the most widely used FSS alloy due to good resistance to stress corrosion cracking. Owing to the chemical composition range, AISI 430 alloys undergo a partial phase transformation of ferrite to austenite when subjected to hot rolling temperatures. Consequently, the alloys consist of ferrite and austenite during processing. The presence of austenite and ferrite influences the microstructure evolution and texture development during hot rolling and subsequent annealing heat treatments. Two AISI 430 FSS heats of varying austenite volume fraction were used in this study. The two AISI 430 FSS heats were deformed using the first three passes of the Steckel mill hot rolling process. Post deformation heat treatments namely: continuous phase transformation and martensite tempering heat treatments were performed after three successive simulated Steckel mill passes. Microstructure analyses were performed using light microscopy and Electron Backscattered Diffraction (EBSD). The microstructure analyses were performed in order to determine microstructure evolution and texture development during hot deformation and post deformation heat treatments. The difference in austenite volume fraction in the respective heats A and B has profound influence on the possibilities for microstructure and texture evolution. For the higher austenite volume fraction heat A, the post-deformation path for austenite decomposition can lead to two very different textures in the prior austenite regions. During continuous diffusional transformation from austenite to ferrite the final texture is influenced by expected variant selection as well as growth selection during the prolonged isothermal heat treatment. The result is relatively strong {001}<110> texture and comparably very weak γ-fiber texture. In the case of the martensite tempering process the γ-fiber texture that is inherited from the austenite to martensite diffusionless transformation is maintained in the prior austenite regions. The mode of post-deformation heat treatment does not significantly impact on texture development in heat B where the texture is dominated by recovery and growth in the primary ferrite phase.